The Effectiveness of Kangaroo Mother Care on Thermoregulation Stabilization in Low Birth Weight Infants - Rahmat Kurniawan; Elsy Dinimayanti; Lenny; T.Iskandar Faisal; Nuswatul Khaira; Alfian Helmi; Siti Kusnul Khotimah; Mursiah Mursiah (LPPM Universitas Harapan Bangsa, 2026)
Introduction: Low birth weight (LBW) infants are at high risk of hypothermia due to immature thermoregulation mechanisms. Kangaroo Mother Care (KMC), characterized by continuous skin-to-skin contact, is recommended as a simple and cost-effective intervention to maintain thermal stability. This study aimed to determine the effectiveness of KMC in stabilizing body temperature among LBW infants in a perinatology ward. Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted from December 2022 to January 2023 in the Perinatology Room of Tangerang Hospital, Tangerang City. A total of 40 LBW infants were recruited using total sampling. Body temperature was measured using a digital thermometer before and after KMC implementation. Data were analyzed using a paired t-test with a significance level of p < 0,05. Results: Prior to KMC, 87,5% of infants experienced hypothermia, while only 12,5% had normal body temperature. After KMC intervention, 100% of infants achieved normal temperature ranges (36,5°C–37,3°C). Statistical analysis showed a significant difference in mean body temperature before and after KMC (p = 0,001), indicating that KMC effectively improved thermoregulation in LBW infants. Conclusion: Kangaroo Mother Care significantly enhances thermal stability in low birth weight infants and can be implemented as a safe, non-invasive, and low-cost intervention in perinatology settings. Integrating KMC into standard neonatal care protocols may contribute to reducing hypothermia-related complications and improving neonatal outcomes.